Gratification of Ticketing and Accommodation Facilities by the Former Deputy Chairman of the Kpk Reviewed Law Number 19 of 2019 Concerning the Second Amendment to Law Number 30 of 2002 Concerning the Corruption Eradication Commission - Brian Rommy Sitorus; Abdul Hakim; Maya Jannah (Journal of Social Research, 2023)
Not enough with one ethical violation, KPK leader Lili Pintauli again acted and again dealt with the KPK Supervisory Board (Dewas) over the alleged receipt of gratuities in the form of hotel accommodation to tickets to watch the Mandalika MotoGP. This study aims to find out and analyze the regulation of gratification as one of the criminal acts of corruption. And knowing and analyzing about gratification can be classified as a criminal act of bribery corruption. This research belongs to the normative type of research. So it can be known that the regulation of gratification as one of the criminal acts of corruption in accordance with the value of life in Indonesia, that gratification is not essentially a criminal act. Because gratification is inseparable from the habits of people who have been cultured. In addition, gratuities can be classified as criminal acts of bribery corruption, if the gratuities are given to civil servants / State administrators/officials related to their positions. The receipt of such gratuities is contrary to the obligations or duties of the state administrator.